Atypical Presentation of Lemierre’s Syndrome Causing Septic Shock and Acute Respiratory Distress Syndrome - Divyesh Reddy Nemakayala; Manoj P Rai; Shilpa Kavuturu; Supratik Rayamajhi (Case Reports in Infectious Diseases)
Lemierre’s disease is a rare but life-threatening condition characterized by an oropharyngeal infection complicating with thrombophlebitis of the internal jugular vein and disseminated abscesses. We are presenting a case of a young female who initially presented with fevers, chills, sore throat, and swollen neck later developed progressively worsening shortness of breath along with sudden onset pleuritic chest pain. She then developed progressively worsening acute hypoxic respiratory failure requiring intubation and mechanical ventilation. Interval chest X-ray showed worsening bilateral effusions. She also developed septic shock requiring pressors. Blood culture showed Fusobacterium, and antibiotics were changed accordingly following which there was a clinical improvement. The diagnosis of Lemierre’s syndrome was then established based on her presenting age and bilateral pulmonary empyema in the setting of septicemia with Fusobacterium.